2020
DOI: 10.5114/aoms.2020.97053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of childhood overweight and obesity on foot and lower limb pain in a population of primary school children

Abstract: Introduction: In childhood, juvenile obesity affects the functional characteristics of the lower limb, predisposing children to pain, discomfort and musculoskeletal comorbidities. This cross-sectional descriptive study analyses the relationship between childhood overweight/obesity and foot/lower limb pain in a population of primary school children. Material and methods: The study population consisted of 150 children aged 9-12 years recruited at a primary school in Malaga (Spain). None had pathologic feet. Anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…A thicker fat pad increases the amount of deformable soft tissue forming a larger contact area and a higher pressure on the foot [ 39 41 ]. As a higher body weight is speculated to influence lower limb muscle activities [ 42 ] and pain in the foot and lower limbs [ 43 ], the weight-related flattening of MLA gives further insight on the differential muscle activation patterns in children with DCD during walking [ 3 ]. Whether a higher body weight and total fat percentage have comparable effects on plantar pressure and structure remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A thicker fat pad increases the amount of deformable soft tissue forming a larger contact area and a higher pressure on the foot [ 39 41 ]. As a higher body weight is speculated to influence lower limb muscle activities [ 42 ] and pain in the foot and lower limbs [ 43 ], the weight-related flattening of MLA gives further insight on the differential muscle activation patterns in children with DCD during walking [ 3 ]. Whether a higher body weight and total fat percentage have comparable effects on plantar pressure and structure remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated to a chronic low-grade inflammatory state, whose effects affect almost all organ systems, with an increased risk of endocrine, cardiovascular, gastrointestinal, reproductive, pulmonary, musculoskeletal, and psychological complications [ 17 , 30 ]. They include hypertension, dyslipidemia, hyperinsulinemia, type 2 diabetes mellitus, cardiovascular disease, nonalcoholic fatty liver disease (NAFLD), nonalcoholic steatohepatitis (NASH), cholelithiasis asthma, sleep apnea, osteoarthritis, hyperandrogenemia, polycystic ovarian syndrome (PCOS), foot and lower limb pain, and musculoskeletal comorbidities [ 2 , 31 , 32 ].…”
Section: Pediatric Obesitymentioning
confidence: 99%
“…Obesity is a complex, many-faceted status that exposes the pediatric patients to a wide spectrum of inflammatory, metabolic, and endocrine dysfunctions, which influence and enhance each other through biochemical and molecular interactions [1]. Pediatric obesity exposes the affected subjects to a higher risk of short-and long-term complications, such as type 2 diabetes (T2DM), dyslipidemia, nonalcoholic fatty liver disease (NAFLD), obstructive sleep apnea (OSA), asthma, polycystic ovary syndrome (PCOS), musculoskeletal comorbidities [2], and adolescents with obesity are at increased risk of psychological disturbances [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The average static plantar pressure in children with diplegic and hemiplegic CP was higher on the forefoot and midfoot regions, while lower on the rearfoot region [ 6 ]. In addition to plantar pressure distribution, foot posture index (FPI), heel and knee alignment are considered to be the key factors of affecting foot pressure and the feasible methods to assess variations of the angle and motion behavior of lower extremities and lower limb defects [ 20 , 21 ]. As in the study by Yan et al [ 22 ], they observed that children experienced unstable walking due to a flatter foot and a larger foot axis angle as well as altered foot pressure while walking, compared with non-obese children.…”
Section: Introductionmentioning
confidence: 99%